The Effect of Education Giving on The Parent's Behavior About Growth Stimulation in Children with Stunting - Febrina Suci Hati; Arantika Meidya Pratiwi (NurseLine Journal, 2019)
Stunting (short body) is a very short body state that goes beyond 2 SD below the median length or height of the population body which is an international reference. Stunting describes a lack of nutrition that has been going on for a long time and requires time for children to develop and recover. A number of studies show a link between Stunting with poor motor and mental development in early childhood, and poor cognitive achievement and school achievement in late childhood. In Sleman Regency in 2014 the Stunting number reached 12.87% (DIY 14.32%), wasting 4.02% (DIY 3.89%) and overweight 5.82% (DIY 5.84%). The highest Stunting rate appears in the Margins of 141 toddlers experiencing Stunting. Of all the toddlers in existence, and as a cause of malnutrition cases are the presence of comorbidities, congenital abnormalities from birth and because of wrong care. Parents of children with Stunting have focused on treatments to restore anthropometric growth but are less aware of the stimulation efforts that need to be done. The purpose of this study was to provide a design intervention in midwifery care in children with Stunting by providing education to parents about the stimulation of growth and development. The research method uses quasi-experimental pre-post test with control group design. Data analysis was carried out by Paired T-Test analysis. Respondents in this study were mothers with 1-3 year old stunting children in Sleman Regency. The sampling technique used in this study was using purposive sampling technique. The number of samples in this study was 37 people. The results showed that there was an effect of providing education on the stimulation of child growth and development of parents' children with Stunting with a significance value of p = 0.002 (p <0.05). There is are the influence of education giving on the parent's behavior about growth stimulation in children with stunting.